2016
DOI: 10.3892/ol.2016.5382
|View full text |Cite
|
Sign up to set email alerts
|

DHA blocks TPA-induced cell invasion by inhibiting MMP-9 expression via suppression of the PPAR-γ/NF-κB pathway in MCF-7 cells

Abstract: Docosahexaenoic acid (DHA) is an omega-3 fatty acid that is considered to have applications in cancer prevention and treatment. The beneficial effects of DHA against cancer metastasis are well established; however, the mechanisms underlying these effects in breast cancer are not clear. Cell invasion is critical for neoplastic metastasis, and involves the degradation of the extracellular matrix by matrix metalloproteinase (MMP)-9. The present study investigated the inhibitory effect of DHA on MMP-9 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Dietary supplementation of fish oil rich in EPA and DHA decreases breast cancer metastasis in a mouse model, as well as attenuating cancer cell migration and invasion in vitro by downregulating expression of CD44, a cell surface protein which binds matrix collagen and MMP‐9 to facilitate ECM remodeling . DHA also directly blocks MMP‐9 expression by suppressing the PPAR‐γ/NF‐κB pathway . Interestingly, DHA has no effect on the viability of the MCF‐7 cells used in this study, although another study reported that DHA induced ROS‐mediated apoptosis in MCF‐7 cells, perhaps due to differences in the concentrations used.…”
Section: Fatty Acidsmentioning
confidence: 69%
“…Dietary supplementation of fish oil rich in EPA and DHA decreases breast cancer metastasis in a mouse model, as well as attenuating cancer cell migration and invasion in vitro by downregulating expression of CD44, a cell surface protein which binds matrix collagen and MMP‐9 to facilitate ECM remodeling . DHA also directly blocks MMP‐9 expression by suppressing the PPAR‐γ/NF‐κB pathway . Interestingly, DHA has no effect on the viability of the MCF‐7 cells used in this study, although another study reported that DHA induced ROS‐mediated apoptosis in MCF‐7 cells, perhaps due to differences in the concentrations used.…”
Section: Fatty Acidsmentioning
confidence: 69%
“…To further investigate the detailed anti‐invasive mechanism of mLU8C‐PU, we examined several transcription factors, including AP‐1 and NF‐ĸB. AP‐1 and STAT3, well‐known regulators of the transcription of MMP‐9, IL‐8 and have been regarded as targets for screening new anti‐invasive drugs . In our study, TPA‐induced nuclear translocations of AP‐1 and NF‐ĸB were suppressed when MCF‐7 cells were pretreated with mLU8C‐PU.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it should be considered that neither T3 nor the AMPK inhibitors used by the authors are drugs specifically designed to regulate inflammasome action. Another experimental strategy involved administering of docosahexaenoic acid, a main component of Omega (ω)-3 polyunsaturated fatty acids, which protects against I/R damage in livers undergoing 30 min of total warm I/R injury [125,126]. Evaluating the contribution to inflammasome regulation, the authors suggest that the underlying mechanisms of docosahexaenoic acid include activation of PI3K/Akt pathway and the inhibition of proteins such as NLRP3, ASC and cleaved caspase-1 involved in pyroptosis, a highly inflammatory form of non-apoptotic and caspase-1-dependent programmed cell death [126,127].…”
Section: Relevance Of Inflammasome In Hepatic Ischemia-reperfusionmentioning
confidence: 99%